(untitled) (Tempo e Argumento, 2010)
The aim of this paper is to study different aspects of female religious training from the perspective of the sensibilities and discipline. For this we present testimony from women who went through the training process in the CIIC. The statements put together with the dialogue and with the training manuals build a rather large scenario, which offers an insight into the construction of meaning and vocations to the later work institutionally linked to the Catholic Church.